2015
DOI: 10.1007/s13337-015-0274-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study indicates nearly a quarter of sheep population in Karnataka state of India is infected with ovine herpesvirus 2

Abstract: In a cross-sectional study, prevalence of ovine herpesvirus 2 (family: Herpesviridae, subfamily: Gammaherpesvirinae, genus Macavirus and species: Ovine herpesvirus 2) infection was estimated in sheep population of Karnataka state in India. Based on the three stage cluster sampling method, whole blood samples (356) of sheep were collected from 11 sheep-dense districts of the state. The samples were tested for presence of OvHV-2 genome by recommended hemi-nested polymerase chain reaction (PCR) test. The true pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The farmer was unwilling for a postmortem. In previous study, progression of corneal edema correlated well with disease outcome, and that non improvement of uveitis was considered as a bad prognostic sign [3]. The same was observed in this case study also.…”
Section: Resultssupporting
confidence: 88%
“…The farmer was unwilling for a postmortem. In previous study, progression of corneal edema correlated well with disease outcome, and that non improvement of uveitis was considered as a bad prognostic sign [3]. The same was observed in this case study also.…”
Section: Resultssupporting
confidence: 88%
“…It is possible that the calf acquired the OvHV-2 infection from either of these two sheep, because calf had no history of common grazing with animals of other farms. Based on a few molecular epidemiology studies (by RT-PCR) on OvHV-2 that have been conducted so far in India, the prevalence of OvHV-2 in sheep varied from 24.44% to 85%, the highest being in the Northern part of India and the lowest in the Southern part of India ( 10 , 12 , 14 ). It may be noted that these differences arising from the different grographical regions may likely be due to false-negative results in RT-PCR assays, due to the low viral load in blood of the latently infected individual animals from reservoir species (sheep and goats).…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of SA-MCF disease by OvHV-2 genome detection in sheep and goat (10), captive bison (11), and cattle (12,13) has since then been reported. The prevalence of OvHV-2 in sheep ranged from 24.44% to 85% in various states in India (10,12,14) however, the genetic characterization of OvHV-2 was not reported in any of these studies. In the present study, we report an investigation of SA-MCF disease in a cattle calf and asymptomatic infection in the in-contact reservoir hosts (sheep and goat) that occurred on a farm located at Tirunelveli, Tamil Nadu, India.…”
Section: Introductionmentioning
confidence: 91%
“…Kumar et al (2014) also reported an outbreak of SA-MCF in cattle in a village in Andhra Pradesh in which thirteen adult cows and two calves died out of a population of forty animals. Recently, Premkrishnan et al (2015) reported that nearly a quarter of sheep population in Karnataka state of India is infected with OvHV-2. The disease is generally infrequent in countries where Bos indicus and Bos taurus are predominant species.…”
Section: Epidemiologymentioning
confidence: 99%
“…Sheep associated MCF is a particular problem in farmed bison, deer and Bali cattle (Li et al 2006, Russell et al 2009. It is also enzootic in India where sheep are raised (Wani et al 2004, Vinod et al 2014, Premkrishnan et al 2015. MCF is a very complex disease and is difficult to control as the infections are symptomless and widespread in reservoir hosts.…”
mentioning
confidence: 99%